Kakšna naj bi bila integracijska politika? - Komac, Miran (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The Republic of Slovenia is a multi-ethnic community. Inhabitants that declare themselves as Ćnon-SloveniansĆ wish to preserve - according to their opinion leaders - the basic elements of their original national identity. However, the majority/dominant population is reserved, often even negative, towards public manifestations of ethnic diversity. The key question here is: how to ensure equal status of members of ĆnewĆ minority communities, which are neither recognized in terms of constitution, nor treated as ethnic communities in Slovenia, and how to respect their need to preserve ethnic features. Which integration model would be most suitable for this situation, and what would be the key elements of such integration? To acquire sufficient information on perceptions, needs and wishes of Slovene people, concerning integration policy, the project Perceptions of Slovene Integration Policy was launched. On the basis of results of empirical research, relevant data for the upgrading/operationalization of the existing Slovene integration policy were gained.
Keywords: Slovenia; Slovenija; narodne skupnosti; manjšine; etnične manjšine; integracijska politika; priseljenci